Twenty Years after: Statute of Limitations and the Asymmetric Burdens of Justice in Northern Ireland and Post-war Germany. Issue 4 (3rd September 2020) - Chung, C K Martin
Abstract: In 2018, that is 20 years after the conclusion of the Belfast Agreement ending the 30-year conflict in Northern Ireland known as the 'Troubles', the UK Government started a consultation on dealing with its legacy. The House of Commons Defence Committee proposes the enactment of a statute of limitations to shield veterans from further investigations into Troubles-related crimes. It would represent a 'balanced' approach to justice, as some paramilitary combatants had also received de facto amnesty through various schemes. This article argues that given the involvement of the British state in the historical conflict, a 'balanced' approach to dealing with the past is inadequate. Drawing on parallel parliamentary debates in Germany that began around 1965, that is also 20 years after the end of conflict, the article makes the case that an asymmetric approach is both promising and necessary for the reconciliation process to move forward.